2016
DOI: 10.1007/s00268-016-3820-7
|View full text |Cite
|
Sign up to set email alerts
|

Thromboembolic Prophylaxis with Heparin in Patients with Blunt Solid Organ Injuries Undergoing Non‐operative Treatment

Abstract: Background: Patients with blunt solid organ injuries (SOI) are at risk for venous

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…25 While there has been no randomized trial comparing early and late initiation of VTE prophylaxis in SOI, there have been several observational studies comparing early (typically <48 hours after injury) with late (>48 hours after injury) initiation. [26][27][28][29][30][31][32] Uniformly in these studies, there has been no increase in postprophylaxis transfusion requirements or failure of non-operative management requiring intervention. Therefore, it appears that institution of VTE prophylaxis in patients with blunt SOI is safe and may be performed within 48 hours from the time of injury in the absence of ongoing bleeding.…”
Section: Discussionmentioning
confidence: 90%
“…25 While there has been no randomized trial comparing early and late initiation of VTE prophylaxis in SOI, there have been several observational studies comparing early (typically <48 hours after injury) with late (>48 hours after injury) initiation. [26][27][28][29][30][31][32] Uniformly in these studies, there has been no increase in postprophylaxis transfusion requirements or failure of non-operative management requiring intervention. Therefore, it appears that institution of VTE prophylaxis in patients with blunt SOI is safe and may be performed within 48 hours from the time of injury in the absence of ongoing bleeding.…”
Section: Discussionmentioning
confidence: 90%
“…Recently, the optimal time to initiate VTE chemoprophylaxis after blunt solid organ injury has been an area of active research focus. A number of prospective [3] and retrospective [4][5][6][7][8][9][10][11][12] studies have demonstrated that VTE chemoprophylaxis administration 24-48 hours after arrival to the Emergency Department (ED) is associated with reduced rates of VTE without increased need for blood transfusion or failure of nonoperative management. On this basis, we hypothesize that VTE chemoprophylaxis initiated ≤48 hours of ED arrival is safe and effective at preventing VTEs without an associated increased need for blood transfusion.…”
Section: Introductionmentioning
confidence: 99%
“…Bleeding and failure of NOM are among the feared complications of starting CTP in patients with SOI. Most of the current studies that assessed the safety of early vs late CTP did not find any difference between the two regarding the rates of bleeding complications or failure of NOM (16,(25)(26)(27). However, the two biggest limitation for these studies were inadequate power and the lack of a control group (i.e.…”
Section: Discussionmentioning
confidence: 82%
“…A recent study from Switzerland by Khatsilouskaya et al analyzed the safety and efficacy of CTP. In their analysis of 179 adult trauma patients with SOI with NOM, they did not find any difference between early, late or no-CTP group regarding the rate of VTE complications (16). Similarly, another study by Joseph et al analyzed 145 trauma patients with SOI who underwent NOM and received CTP with LMWH (25).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation